14-3-3ζ-A Novel Immunogen Promotes Inflammatory Cytokine Production - McGowan, Jenna; Peter, Cara; Chattopadhyay, Saurabh; Chakravarti, Ritu (Frontiers in Immunology, 2019)
The presence of autoantibodies against 14-3-3z in human autoimmune diseases indicates its antigenic function. However, neither the cause nor the consequence of this newly-identified antigenic function of 14-3-3z protein is known. To address this, we investigated the immunological functions of 14-3-3z by studying ex vivo effects on human peripheral blood mononuclear cells (PBMC) proliferation, polarization and cytokine production. Exogenous 14-3-3z promoted PBMC proliferation and T cell polarization towards increasing Th1 and Th17 populations. Significant increases in IFN-g and IL-17 levels were observed in the presence of 14-3-3z. A specific increase in Th1 cells and IFN-g production provided strong evidence for MHC class II presentation of 14-3-3z antigen. Particularly HLA-DRB1*0401 allele strongly promoted 14-3-3z-induced IFN-g producing cells. In contrast, prednisolone treatment inhibited 14-3-3z-induced both T cell polarization and cytokine production. Overall, we show that MHC presentation and adaptor functions of 14-3-3z participate in promoting IFN-g and IL-17 production, two of the cytokines commonly associated with autoimmune diseases. To the best of our knowledge, this is the first report describing the ex vivo antigenic function of 14-3-3z with human PBMC, thereby providing the basis of its immunological role in human diseases.